Performance Measurement System Design with Balanced Scorecard Method at PT. Z - Yudi Daeng Polewangi; Nukhe Andri Silviana; Agustinus Silaban (Budapest International Research in Exact Sciences (BirEx) Journal, 2021)
This study aims to determine the performance of PT. Z with a Balanced Scorecard approach for the 2016-2020 period based on four perspectives, namely Finance, Customers, Internal Business Processes, and Learning and Growth. The results of this study provide evidence that the Financial Perspective can be said to have been well characterized by an increase in the amount of income, total net income, total equity, and total assets owned. Judging from the financial ratios used (ROE, ROA, and BOPO), it shows that in general there is also an increase. From the customer perspective, consumers are quite satisfied with the service so far in terms of customer satisfaction attributes, interest in innovation changes, and company image. Overall the performance of PT. Z from an Internal Business Process Perspective on the innovation side is very bad with no product innovation being carried out from 1990-present. Meanwhile, in terms of operating processes, the company has implemented process time efficiency well. From the perspective of training and development, based on the results of interviews with company leaders, the company has never conducted training and development for employees. Judging from the job satisfaction indicator in the learning and growth perspective, the average overall employee answer is 3.74, this means that the employees of PT. Z felt quite satisfied while working at PT. Pabrik Es Siantar.